2016
DOI: 10.1111/liv.13205
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive fibrosis score for hepatitis delta

Abstract: Existing non-invasive fibrosis scores are either impracticable or do not perform well in chronic hepatitis delta patients. However, the new Delta Fibrosis Score is the first non-invasive fibrosis score specifically developed for chronic hepatitis delta and requires only standard parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 36 publications
3
62
3
1
Order By: Relevance
“…This prevalence was up to 40% in a European study that included genotype-1 HDV patients [19] and up to 53% in multi-center study in Italy [1]. The present study reported a higher prevalence of severe liver disease in chronic HDV infection than those series.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…This prevalence was up to 40% in a European study that included genotype-1 HDV patients [19] and up to 53% in multi-center study in Italy [1]. The present study reported a higher prevalence of severe liver disease in chronic HDV infection than those series.…”
Section: Discussioncontrasting
confidence: 41%
“…However, these serological biomarkers use platelet count in theirs formulas and most patients with chronic HDV infection have splenomegaly and hypersplenism leading to thrombocytopenia that might overestimate liver fibrosis by methods. In addition, those serological markers had a not satisfactory diagnostic performance (AUROC < 0.80) in HDV infected patients using liver biopsy as the reference [19]. The same authors have proposed a new biomarker, Delta Fibrosis Score, that uses levels of cholinesterase, GGT and albumin combined to age, for prediction of liver fibrosis in HDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent piece(6) reporting on 100 subjects from HIDIT-1, similar results were described. Despite these low numbers, it should be noted that the WHO has estimated that only 5% of HBsAg positive individuals are co-infected with HDV globally and both the US FDA and European Medicines Agency (EMA) consider HDV to be a rare disease allowing novel therapies in this field for orphan drug designation.…”
supporting
confidence: 72%
“…Our study shows that the combined quantitative profiling of HBV and HDV markers identifies specific patterns associated with activity and stage of CHD and confirms the relevance of an underlying transcriptionally active HBV infection for HDV pathogenicity, in spite of the inhibition on HBV replication exerted by HDV. At present, in clinical practice, the best prognostic scores to identify candidates to antiviral therapy are based on algorithms using early markers of advanced fibrosis . Therefore, there is an unmet need to identify predictors of unfavourable disease outcome independent of markers which are already consequence of advanced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%